PENGARUH MODEL DISCOVERY LEARNING BERBANTUAN MEDIA GAMBAR BERSERI TERHADAP KETERAMPILAN MENULIS TEKS CERPEN SISWA KELAS VII SMP NEGERI 2 KOTA SOLOK - Pratiwi, Ririn; Gani, Erizal; Tressyalina, Tressyalina (Universitas Negeri Padang, 2016)
ABSTRACTÂ The purpose research of this describe the impact of the discovery learning aided the media images glow of skill write the text short story class VII SMP Negeri 2 Kota Solok. This type of this study is quantitative methods of experimentation. The result of this research there were three, which is (1) the skill of the text short story class VII SMP Negeri 2 Kota Solok before using the model discovery learning aided the media image series are at sufficient qualifications (C) with an average of 60,59, (2)the skill of writing text short story class VII SMP Negeri 2 Kota Solok after using the model discovery learning aided the media image series is in the qualifications either (B) whit an average 78,89, (3) the skill of writing text story class VII SMP Negeri 2 Kota Solok after using the model discovery learning aided the media image glow is better than before using the model discovery learning aided the media image.Â Kata kunci: pengaruh, discovery learning berbantuan media gambar berseri, teks cerpen